AYATU'S-SIYAHA FI'L-KUR'ANI'L-KERIM DIRASE MEVDUIYYE - AHMED, KHALIS HASAN (Fırat Üniveristesi, 2017)
Bu araştırmada müfessirlerin seyahatle ilgili ayetleri nasıl tefsir ettikleri incelenmiştir. Girişte seyahat kelimesinin lügat ve ıstılahi manaları açıklanmış, daha sonra seyahat kelimesinin Kur'an'daki manaları üzerinde durulmuştur. Özellikler Tevbe suresindeki ayetin manası hususunda müfessirlerin farklı görüşleri zikredilmiştir. Bazı müfessirler ayetteki seyahat kelimeini oruç olarak açıklarken bazıları cihad, diğer bazıları da yolcular manasında olduğunu belirtmişlerdir. Ayrıca bu araştırmada seyahatin önemi ve müfessirlerin bu konudaki görüşleri delilleriyle birlikte zikredilmiştir. Araştırmada seyahat kelimesinin eş anlamlıları geçtiği sıyak içindeki manaları ile birlikte açıklanmıştır. Yolcuların namazı kısaltmaları, suyun bulunmadığı veya kullanımının zor olduğu yerlerde teyemmüm almanın caiz oluşu, meşru seyahatlerde ramazan günlerinde iftar etmenin caiz oluşu gibi birtakım şerî hükümler de açıklanmıştır. Araştırmada elde edilen neticeler zikredilerek tezde istifade edilen kaynaklar gösterilerek tez bitmiştir. Anahtar Kelimeler: Seyahat, yolculuk, dinlenme, kolaylık

We attempt to explore the views of the commentators in the verses of tourism, we began paving and prefacing the meaning of tourism through the linguistic and idiomatically illustration, and showing their meanings in the Holy Qur'an, especially they did not confirm to the word about the commentators of the intend meaning of them in the Sura "Repentance". Some of them said as the sense of fasting, and some of them said as the sense of jihad and others saw as meaning travelers and so on, then the research shows the importance of tourism and the views of the commentators in with a statement of the evidence and arguments for each team, as the researcher demonstrated to find synonyms for the word of tourism, the meaning of each synonym in the context which it was stated, and between, then spoke find legal provisions relating to tourists shorten the pray and acceptable ablution "Tayammum" when water loss or difficulty of use or get it, and it's acceptable at the day time, especially, during the day in Ramadan when legitimate tourism that are not punctuated sins and transgressions, at conclusion I explained the most important findings and proved in the end of the search list of major sources and references that drew them most of the scientific research article. Key Words: Tourism, Travel, Entertainment, Easing
Tourism in the verses of the Holy Quran
Keywords: Din